Evapotranspiração de referência no semiárido brasileiro, análise de modelos, sensibilidade e tendência dos elementos climáticos - Lima Junior, Juarez Cassiano de (2022)
Simplified models can be used to estimate evapotranspiration when there is data limitation, and the Hargreaves and Samani equation is one of these options, however, this ease makes calibration necessary to improve your estimates. In addition, the sensitivity and trend analysis of temporal changes in climatic elements is important for understanding the relevance of climatic elements for estimating reference evapotranspiration, as well as providing information on water demand in agriculture and water resources management. Thus, this study aimed to improve the precision of estimates using the modified Hargreaves and Samani equation, starting from a set of climate data from a period covering 1961 to 2021, taken from 97 meteorological stations located in the Brazilian semiarid region and its Also, analyze the sensitivity and trend of climatic elements and reference evapotranspiration in the Brazilian semiarid region. Among the proposals suggested by the present work, the best results were obtained with the inclusion of wind speed and relative air humidity, both with adjusted coefficients: the agreement of the estimates increased and the square root of the mean error decreased. The adjusted option that had wind speed inserted presented a rating varying between “Excellent” and “Very good” for 91% of the locations studied, while the option in which relative air humidity was inserted, 74% of the locations had the same classification. Regarding sensitivity, for evapotranspiration estimated with the standard model, the least sensitive element was wind speed, and the most important elements were maximum and average air temperatures. Regarding the trend, an increase in air temperatures was observed in general, for reference evapotranspiration, 54 locations were observed with a positive trend, while for rain, a negative trend was observed in 54 locations, with 9 of these being significant.